Resilience and caregiving ability among caregivers of people with stroke: The mediating role of uncertainty in illness - Wang, Jinyao; Cui, Jun; Tu, Shuangyan; Yang, Rong; Zhao, Lihong (Frontiers in Psychiatry, 2022)
Background In China, stroke survivors are usually cared for by family members. The caregiving ability of these informal caregivers remains inadequate during the hospital stay after the sudden stroke onset of their family members, and the sudden care burden continues to overwhelm caregivers even after the hospital discharge. Research is needed to examine predictors of caregiving ability, which could be targeted in future interventions aiming to improve caregiving skills and reduce the burden of caregivers who care for stroke survivors. Materials and Methods Stroke survivors who were hospitalized for the first time and their family caregivers were enrolled by convenience sampling from August 2019 to February 2020. Caregiver demographic information, resilience status, uncertainty in illness, and caregiving ability, as well as patients’ severity of stroke were measured using standardized questionnaires. Structural equation modeling was used to test the proposed model, whereby caregiver resilience and severity of stroke predicted caregiving ability directly, and uncertainty in illness mediated the association between caregiver resilience and caregiving ability. Results A total of 306 dyads were included in the study. The tested model provided a good fit to the data (χ2=118.2, df=64, RMSEA=0.053, CFI=0.946, TLI=0.923). Statistically significant pathways linked caregivers’ resilience status to uncertainty in illness (β=-0.558, S.E.=0.022, P<0.01), caregivers’ resilience to status caregiving ability (β=-0.269, S.E.=0.013, P<0.01) and caregivers’ uncertainty in illness to caregiving ability (β=0.687, S.E.=0.051, P<0.01). We also found that caregivers’ uncertainty in illness mediated the association between caregivers’ resilience and their caregiving ability (β=-0.384, S.E.=0.061, P<0.01). Conclusions Our structural equation modeling result identified resilience and uncertainty in illness as predictors of the caregiving ability of informal family caregivers who suffered from care burdens. Supporting family caregivers to build their resilience and reducing their uncertainty in illness may be ways to improve their caregiving for stroke survivors.